Congenital rubella syndrome and its protean manifestation in Nigeria - Nubwa Yusufu Papka; Chinwe Chioma Okoro; Esther Anani; Maryam Abdulrahman Raji; Josephat M. Chinawa (SpringerOpen, 2024)
Abstract Background Congenital rubella syndrome (CRS) arises from intrauterine infections with the rubella virus especially during the first trimester of pregnancy. It affects various systems resulting in disastrous outcomes. Case presentation We present four cases of congenital rubella syndrome each manifesting a constellation of clinical features, some of which are cross-cutting with the aim of raising awareness among clinicians who may be involved in its management. Conclusion Congenital rubella syndrome is a deleterious condition with protean manifestations as demonstrated by the series presented in this report. The burden of CRS in developing countries still exists and can be curbed via immunization programme, introduction and strengthening of surveillance programme.